Supplementary Material for paper "Robust Spatial Estimates of Biomass Carbon on Farms" - Beka, Stelina (Cranfield University, 2022)
The series of datasets in this document were used during the development of two probabilistic spatial models described in the paper.
Keywords: Spatial Bayesian'; 'biomass C'; 'Farm management'